1991
DOI: 10.1073/pnas.88.16.7106
|View full text |Cite
|
Sign up to set email alerts
|

The low-affinity p75 nerve growth factor (NGF) receptor mediates NGF-induced tyrosine phosphorylation.

Abstract: Protein tyrosine phosphorylation is a potential mechanism for initial sinaling in PC12 cells during dfferentiation in response to nerve growth factor (NGF). NGF-induced tyrosine phosphorylation has been found to be initiated by the trk protooncogene, which participates in the formation of highaffinity NGF binding sites. In contrast to transfection of wildtype low-affinity p75 NGF receptors, transfection of p75NGm with mutations in the cytoplasmic domain resulted in an inability of NGF to elicit tyrosine phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
85
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(95 citation statements)
references
References 43 publications
(56 reference statements)
10
85
0
Order By: Relevance
“…This view is supported by transfection studies, in which introduction of p75NGPR restores high-affinity binding in mutant cells lacking this protein and also allows NGF-induced protein phosphorylation (12)(13)(14). On the other hand, attempts at crosslinking the two receptors have so far failed (15), and they do not coimmunoprecipitate (9, 16).…”
Section: Introductionmentioning
confidence: 58%
“…This view is supported by transfection studies, in which introduction of p75NGPR restores high-affinity binding in mutant cells lacking this protein and also allows NGF-induced protein phosphorylation (12)(13)(14). On the other hand, attempts at crosslinking the two receptors have so far failed (15), and they do not coimmunoprecipitate (9, 16).…”
Section: Introductionmentioning
confidence: 58%
“…Association with gpl40trk subunits has been highly controversial despite evidence of participation by NTR in high-affinity complexes (Berg et al, 1991;Hempstead et al, 1991;Battleman et al, 1993;Benedetti et al, 1993;Barker & Shooter, 1994;Hantzopoulos et al, 1994;Mahadeo et al, 1994;Wolf et al, 1995). Failure of chemical crosslinking to reveal a physical complex between NTR and gpl40trk (Meakin & Shooter, 1991) and a report that gpl40trk homodimers account for NGF signaling (Jing et al, 1992) have suggested that NTR does not form a heterodimer with gpl4Otrk.…”
Section: Applications Of the Modelmentioning
confidence: 99%
“…In PC12 cells, NGF binding to p75 NTR enhances NGF-TrkA binding, TrkA autophosphorylation, and biological responses of TrkA (Berg et al, 1991;Barker and Shooter, 1994). p75 NTR signaling may also suppress certain aspects of TrkA activation required for neurite outgrowth.…”
Section: Modulation Of P75 Ntr Signaling By Trka and Vice Versamentioning
confidence: 99%